Construction diploma design on VIM-technology - Druzhinin, Anatoly; Davidenko, Oksana (Transfer of innovative technologies, 2021)
The development of the construction industry of Ukraine as a basis for economic transformations through the introduction of information technology (IT), put forward appropriate requirements for specialists. There is a need at the state level to solve the problem of need and development in the labor market of competencies of specialists for the construction industry in the implementation of VIM technologies, creating a single information model in the construction of Ukraine, which would combine architectural, design, engineering, cost, ecological components with access to cost-effective decision-making for the life cycle of the object and, accordingly, the introduction of innovative technologies in the education and training of competent professionals.